PARAMETERIZATION OF MICROSTRUCTURES IMAGES OF SPHEROIDAL GRAPHITE CAST IRON ON THE BASIS OF THE GRAPHITE DISTRIBUTION DENSITY FUNCTION OF THE INCLUSIONS SIZE - O. A. Sachek; A. N. Chichko; S. G. Likhouzov; T. V. Matyushinets; O. I. Chichko (Литьë и металлургия)
The possibilities of parameterization of microstructures such as SHG2, SHG4, SHG6, SHG10, SHG12, SHgd15, SHgd25, SHgd45, SHgd90, SHgd180, SHgd360 according to GOST (State All-union standard) 3443–87 based on the microstructures of cast iron with different diameter spheroidal graphite are shown. It is proposed to use the function of the density distribution of graphite inclusions in size for the classification of cast iron microstructures with spheroidal graphite. It is shown that density function of graphite inclusions can be used as a criterion of classification of microstructures of cast iron with spheroidal graphite, that offers new opportunities for the quantitative analysis of relations «microstructure-property» for cast iron with spheroidal graphite.